Using accounting data in cartel damage calculations: Blessing or menace? - Paha, Johannes (European Journal of Law and Economics, 2012)
Standard methods for calculating cartel-damage rely on data of prices charged and quantity sold. Such data may not easily be available. In this paper, it is shown that accounting data can be used for computing a lower bound for cartel-damage. Previous literature indicates that economic profits can hardly be inferred from accounting data. Therefore, it is shown under which econometrically testable assumptions on accounting costs a meaningful lower bound for cartel-damage can consistently be estimated when using accounting data. However, the aggregation-level and the publication-frequency of accounting data pose a challenge to the estimation of cartel-damage. A further challenge is to appropriately reflect the strength respectively effectiveness of the collusive agreement in the specification of any such estimation. © 2011 Springer Science+Business Media, LLC.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Accounting data; Cartel damages; Cartel prosecution; Collusion